A two-dimensional CuII–MnII heterometallic coordination polymer: structure determination using synchrotron X-ray powder diffraction and magnetic properties1. Issue 38 (14th October 2015) - Kalisz, Marguerite; Cassaro, Rafael A. A.; Novak, Miguel A.; Andruh, Marius; Amorim, Helio S.; Vaz, Maria G. F.
<x xml:space="preserve">Abstract</x> The structure of a magnetic two-dimensional CuII–MnII heterometallic coordination polymer was solved by using synchrotron X-ray powder diffraction.